Webinar On Primary and Secondary Education Management In Indonesia and The Philippines: Opportunities For Cooperation Between Educational Units (Lembaga Pengembangan Kinerja Dosen, 2025)
Regulations on the implementation and management of education in Indonesia provide opportunities for cooperation between foreign educational units and Indonesian educational units. The Webinar on the Management of Primary and Secondary Education in Indonesia and the Philippines aims to provide an overview of the management of formal education in Indonesia and the Philippines so that it can inspire educators to initiate cooperation in improving the quality of education in both countries. The webinar was held virtually in a collaborative manner by the Indonesian Teachers Association (IGI) of Serang City, the Community of SMA/SMK/SKH Teachers of Banten Province, and the Islamic Education Management Masters Program of UIN Sultan Maulana Hasanuddin Banten. The webinar was held via the Zoom Cloud Meetings platform on April 18, 2025, starting at 13.00 WIB. The webinar provided participants with an overview of the formal education management system for primary and secondary education levels in both countries so that it could increase knowledge and insight, as well as inspiration for participants in developing competencies in the field of education, including follow-up cooperation between both educational units and the education community.